1980
DOI: 10.1161/01.res.47.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the intact pericardium for cardiac performance in the dog.

Abstract: The significance of the intact pericardium for cardiac performance was examined in 18 open-chest dogs. Myocardial chord lengths (MCL) in the right and left ventricle were measured simultaneously by ultrasonic crystals implanted in the myocardium of the anterior walls. In 14 dogs, the ultrasonic elements were inserted into the myocardium through needle openings in the pericardium (intact pericardium). In four other dogs, the elements were inserted through 6-to 7-cm-long incisions in the pericardium which were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
1

Year Published

1981
1981
2003
2003

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 25 publications
2
24
1
Order By: Relevance
“…If this procedure caused a reduction in the pericardial space, the effects of pericardium on the present results would be enhanced. However, this technique was evaluated by Stokland et al (1980) and Kanazawa et al (1983), who found that it kept the pericardium intact. In the present study, an additional small incision was made in the pericardium for dissecting the right coronary artery near its origin.…”
Section: Discussionmentioning
confidence: 99%
“…If this procedure caused a reduction in the pericardial space, the effects of pericardium on the present results would be enhanced. However, this technique was evaluated by Stokland et al (1980) and Kanazawa et al (1983), who found that it kept the pericardium intact. In the present study, an additional small incision was made in the pericardium for dissecting the right coronary artery near its origin.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of how much care is taken, any experiment in which the pericardium is incised, instruments are placed, and the defect is closed should be assumed to have made some change in pericardial compliance. 20 We made an effort during surgery to minimize such alterations and saw no further change in pericardial compliance throughout the period of data collection. Since this animal model does not permit multiple two-dimensional echocardiographic views, no attempt was made to calculate right or left ventricular volume.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In open-chest dogs at low normal cardiac volumes, this effect is most likely relatively small. At volumes approaching the high end of the physiological range, the left ventricular end-diastolic pressure-volume relation clearly shifts downward and to the right after pericardiectomy; this effect becomes marked at supranormal volumes.…”
mentioning
confidence: 99%